Is Dirham better performed than Dinar in hedging fluctuated prices? / Dziauddin Sharif , Norlina Hazamuri and Mohd Asyadi Redzuan - Sharif, Dziauddin; Hazamuri, Norlina; Redzuan, Mohd Asyadi (Institute of Business Excellent, 2010)
Previous researches had shown that the coinage system can make the whole economic system sustainable rather than fiat money system. Of course the reason for that is the Gold Dinar and Silver Dirham are capable of reducing the fluctuation in goods price, thus it can reduce the inflation and deflation. Despite the fact that the both gold dinar and silver dirham are in a same kind, but they are in a different weight age, hence each of them would bring different result in case of stabilizing or hedging the price fluctuation. The question may arise here is which one of these metal can be a better tool to stabilize or hedge the price fluctuation. As a response to this matter, an empirical study would be carried out to find the answer. Therefore, this study is purposely compared the performance of gold dinar and silver dirham in hedging the price fluctuation, and subsequently to identify which one of these commodity monies could be a better hedging tool.